Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26434/chemrxiv.12142383.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Screening of Curcumin and Its Analogs Against the Spike Surface Glycoprotein of SARS-CoV-2 and SARS-CoV

Abstract: COVID-19, a new pandemic caused by SARS-CoV-2, was first identified in 2019 in Wuhan, China. The novel corona virus SARS-CoV-2 and the 2002 SARS-CoV have 74 % identity and use similar mechanisms to gain entry into the cell. Both the viruses enter the host cell by binding of the viral spike glycoprotein to the host receptor, angiotensin converting enzyme 2 (ACE2). Targeting entry of the virus has a better advantage than inhibiting the later stages of the viral life cycle. The crystal structure of the SARS-CoV (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This is reflected by the fact that these three compounds were favorably sampled at the interface after the reclassified run in each case as the most thermodynamically feasible, but under the sampling conditions of this study (see Table 1 and Figure 1). Although this is the first study that considers the docking of this type of compound at the level of the RBD-ACE2 interface, our results coincide with those obtained by other authors who have found that Ibuprofen can have a docking score considerably better than other NSAIDs compared to proteins associated with SARS-CoV-2 [44], and that some derivatives could effectively interact with protein regions involved in this complex [76]. These NSAIDs drugs exhibited very close Ki.…”
Section: Discussionsupporting
confidence: 89%
“…This is reflected by the fact that these three compounds were favorably sampled at the interface after the reclassified run in each case as the most thermodynamically feasible, but under the sampling conditions of this study (see Table 1 and Figure 1). Although this is the first study that considers the docking of this type of compound at the level of the RBD-ACE2 interface, our results coincide with those obtained by other authors who have found that Ibuprofen can have a docking score considerably better than other NSAIDs compared to proteins associated with SARS-CoV-2 [44], and that some derivatives could effectively interact with protein regions involved in this complex [76]. These NSAIDs drugs exhibited very close Ki.…”
Section: Discussionsupporting
confidence: 89%
“…From another point of view, curcumin reduced the pro-inflammatory cytokines and virus-induced cytokine storm, as well as alleviating lung injury, thereby indicating potential effects in the treatment of COVID-19 [ 237 , 241 ]. According to computational methods, curcumin offers the ability to inhibit the spike protein of SARS-CoV-2 and disrupts viral entry [ 242 ]. Another in silico approach also revealed that curcumin and catechin were used as potential antiviral polyphenols through the dual inhibition of host cell receptors to the virus (mediated by ACE2) and viral protein entry (S-protein).…”
Section: Importance Of Phytochemicals In Combating Covid-19mentioning
confidence: 99%
“…Based on their antiviral and anti-inflammatory effects, some phytochemicals such isoflavones, curcumin and diallyl disulfide, have attracted particular attention to providing novel agents in combating coronaviruses and related complications [ 9 ]. These compounds exert antiviral activities against broad spectrum of viruses including adenovirus, Zika virus, herpes simplex virus type 2 (HSV-2), human papiloma virus (HPV), influenza virus, hepatitis virus, and human immunodeficiency virus (HIV), besides MERS-CoV and SARS-CoV [ 10–12 ]. The Brazilian Ministry of Health, 12 herbal medicines derived from plants that are part of the National List of Medicinal Plants of Interest to the Unified Health System (RENISUS), are available for free in the public health network [ 13 ].…”
Section: Introductionmentioning
confidence: 99%